Heterogeneity and the Public Sector Wage Policy - Pedro Maia Gomes (Institute of Labor Economics (IZA), 2017)
A model with search and matching frictions and heterogeneous workers was established to evaluate a reform of the public sector wage policy in steady-state. The model was calibrated to the UK economy based on Labour Force Survey data. A review of the pay received by all public sector workers to align the distribution of wages with the private sector reduces steady-state unemployment by 1.4 percentage points.
Keywords: E24; E62; J45; 330; public sector employment; public sector wages; public sector wage premium; unemployment; skilled workers; worker heterogeneity